Resistance of lines of winter bread wheat created with the participation of spring-winter hybrids to leaf stead diseases - Solomonov, Ruslan; Kryvenko, Anna (ScienceRise: Biological Science, 2020)
When studying the collection of spring soft wheat of different genetic origin, individual samples that are resistant to pathogens and can be used as sources of resistance to pathogens in their hybridization with winter varieties were selected. The aim of our research was to study the level of resistance to pathogens of leaf-stem diseases of spring-winter hybrids of different generations depending on the winter and spring components of crossbreeding and their genetic origin, as well as the effectiveness of selection on artificial infectious and natural backgrounds to obtain disease-resistant, with a set of economically valuable features and properties. Materials and methods. The main method of creating a new hybrid material is intraspecific hybridization of spring and winter soft wheat, followed by selection of stable genotypes of different generations on natural (against powdery mildew) and artificial infectious (against brown and stem rust) backgrounds. The source of material for the research was a collection of samples of spring soft wheat of different genetic and ecological-geographical origin in the amount of 101 pcs, Lines F3 (18 pcs.), F4 (141 pcs.) and F5 (66 pcs.), Created from combinations crossing of spring samples with varieties of the Breeding and Genetic Institute - National Center for Seed Science and Variety Research, different in biological properties. Evaluation of collection varieties and lines was performed according to the generally accepted methods of variety testing. Result. The results of studying the resistance of F3-5 wheat lines created on the basis of spring-winter hybrids to the main pathogens on a natural and artificially created infectious background are presented. The links between resistance to pathogens and the main economic and valuable traits in wheat lines have been identified. Wheat lines with complex resistance to leaf-stem pathogens were obtained. Conclusions. Dedicated winter bread wheat lines which combine in their genotype relative disease resistance with high productivity. These lines are mainly created from crossing spring specimens of Mexican, Western European, Canadian and Russian origin with local winter varieties